2019
DOI: 10.4209/aaqr.2017.12.0566
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Absorption Ångström Exponent (AAE)-Based Method for Evaluating the Contribution of Light Absorption from Brown Carbon with a High-Time Resolution

Abstract: While brown carbon (BrC) might play a substantially important role in radiative forcing, an estimation of its light absorption contribution with high-time resolution is still challenging. In this study, a multi-wavelength (370-950 nm) Aethalometer was applied to obtain the wavelength dependent light absorption coefficient (σ abs ) of aerosols both before and after being heated to 250°C. An improved absorption Ångström exponent (AAE)-based method was developed to evaluate the contribution of BrC to light absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…This remains true even if we change the real part of refractive index of BC to 1.7 (Figure c) or change the imaginary part to 0.3 (Figure d), or if we adopt the refractive index of 1.95–0.79i. Thus, in agreement with earlier publications (Lack & Cappa, ; Romonosky et al, ; Zhang et al, ), and rounding to the higher one decimal place number, we conclude that the AAE(405/781) of a mixture of BC and spectrally flat organic material is limited by AAEitalicBCitalicOC()4057811.7. …”
Section: Bc‐oc In Internal Mixturesupporting
confidence: 93%
See 1 more Smart Citation
“…This remains true even if we change the real part of refractive index of BC to 1.7 (Figure c) or change the imaginary part to 0.3 (Figure d), or if we adopt the refractive index of 1.95–0.79i. Thus, in agreement with earlier publications (Lack & Cappa, ; Romonosky et al, ; Zhang et al, ), and rounding to the higher one decimal place number, we conclude that the AAE(405/781) of a mixture of BC and spectrally flat organic material is limited by AAEitalicBCitalicOC()4057811.7. …”
Section: Bc‐oc In Internal Mixturesupporting
confidence: 93%
“…It has been shown that this assumption may produce a considerable uncertainty in produced results (Lack & Landridge, ). Others proposed the AAE of BC to be <1 (e.g., Zhang et al, ). The larger BC particles (or aggregates of small particles) may have indeed the AAE values <1 depending on their diameter and refractive index (Figure b).…”
Section: Bc and Aaementioning
confidence: 99%
“…Although experimental investigations and numerical calculations are the methods most commonly used to characterize the AAE BC , several studies also have attempted to use atmospheric observations or improved measurements to obtain the site-specific AAE BC values. , For instance, Yuan et al constrained AAE BC based on a linear relationship found between the measured AAEs and the ratios of organic/BC in the atmosphere . However, the general applicability of this method is debatable.…”
Section: Resultsmentioning
confidence: 99%
“…Taking the correlation between the AAE and OC/BC ratio in this study as an example (Figure S8), the intercept of the equation is 1.19 (AAE BC ), and AAE correlates weakly with the OC/BC ratios ( r = 0.52), which implies large uncertainties would result if the extrapolated intercept is used as a representative value for AAE BC . Several studies have retrieved AAE BC through measurements of thermal-denuded absorption in the atmosphere, , but this approach is constrained by the heating temperature and can be affected by variations caused by coating-composition-dependent absorption efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of AAE BC is critical for the correct attribution of b abs,BC,370 . 67,69 An AAE BC value of 1.0 is oen adopted, despite studies have found it might vary according to the BC core, particle size, morphology, mixing state and coating thickness of the particles. 70,71 The impact of these variables can be approximated by the Mie theory using the aerosol size distribution data.…”
Section: Absorption åNgström Exponent the Absorptionmentioning
confidence: 99%